Chemical composition of brazilian pennyroyal essential oil (Mentha pulegium L.) and evaluation of the antimicrobial effect on Staphylococcus aureus and Escherichia coli - Rosa , Ana Carla Rangel; Lima , Robson Moreira de; Miranda , Giulia Stavrakas; Rangel , Deysiane da Silva; Medeiros , Gabriela dos Santos; Alves , Thalita Cristyne de Oliveira; Couto , Joice Olinda do; Andrade , João Victor; Perin , Isabelle Lucas Braga; Marques , Cecília Fernandes Patta Muller; Verly , Leonardo Bindelli; Santos, Mário Ferreira Conceição (Seven Editora, 2024)
The extraction of the EOs was first obtained by hydrodistillation, then their chemical composition was determined by GC/MS and their antimicrobial activity was evaluated. In the analysis and identification of the hydrodistilled  essential oil of Mentha pulegium L. by gas chromatography and mass spectroscopy, 12 compounds were separated, representing 99.31% of the total mass of the essential oil. The majority component was pulegone (80.553%), other components present in appreciable levels were; Piperitone (5,430%); Cyclohexanone,5-methyl-2-(1-methyl)-,(2R-cis) (3,304%); trans-Isopulegone (2.945%); α-Humulena (1,950%). In addition, the screening of the essential oil reveals that there were appreciable results regarding its antibacterial activity against S. aureus 20 μg/mL and E. coli 2.5  μg/mL  . This result was obtained by the undiluted essential oil. However, more research on the factors that influence the biosynthesis and bioactivity of essential oils is needed as essential oils gain important applications in the food and pharmaceutical industry. DOI:https://doi.org/10.56238/sevened2023.001-009